Electrochemical‐Reduction‐Assisted Assembly of a Polyoxometalate/Graphene Nanocomposite and Its Enhanced Lithium‐Storage Performance. Issue 33 (4th July 2013) - Wang, Shan; Li, Haolong; Li, Shuang; Liu, Fang; Wu, Dongqing; Feng, Xinliang; Wu, Lixin
Abstract Herein, we present an electrochemically assisted method for the reduction of graphene oxide (GO) and the assembly of polyoxometalate clusters on the reduced GO (rGO) nanosheets for the preparation of nanocomposites. In this method, the Keggin‐type H4SiW12O40 (SiW12) is used as an electrocatalyst. During the reduction process, SiW12 transfers the electrons from the electrode to GO, leading to a deep reduction of GO in which the content of oxygen‐containing groups is decreased to around 5 %. Meanwhile, the strong adsorption effect between the SiW12 clusters and rGO nanosheets induces the spontaneous assembly of SiW12 on rGO in a uniformly dispersed state, forming a porous, powder‐type nanocomposite. More importantly, the nanocomposite shows an enhanced capacity of 275 mAh g−1 as a cathode active material for lithium storage, which is 1.7 times that of the pure SiW12. This enhancement is attributed to the synergistic effect of the conductive rGO support and the well‐dispersed state of the SiW12 clusters, which facilitate the electron transfer and lithium‐ion diffusion, respectively. Considering the facile, mild, and environmentally benign features of this method, it is reasonable as a general route for the incorporation of more types of functional polyoxometalates onto graphene matrices; this may allow the creation of nanocomposites for versatile applications, for example, in the fields of catalysis, electronics, and energy storage.